Pengaruh Latihan Aerobik terhadap Peningkatan VO₂ Max Personel PKP-PK - Azka Naufal Qaedi; Rahmawati Sukra; Wahyu dwi Agustini (LPPM Politeknik Pratama, 2025)
This study aims to analyze the impact of aerobic exercise on the improvement of VO₂ Max in PKP-PK personnel at Halim Perdanakusuma Airport. Physical fitness, particularly VO₂ Max, is a crucial factor in supporting the readiness of PKP-PK personnel to handle emergency situations. Aerobic exercises, including activities such as jogging, aerobics, and cycling, were selected as a method to enhance cardiovascular fitness. The results indicate that aerobic exercise has a positive impact on increasing VO₂ Max, although there are challenges in maintaining consistent exercise due to duty schedules, weather conditions, and personnel motivation. Based on interviews and observations, it was concluded that structured aerobic exercise can enhance the physical endurance of PKP-PK personnel, which is vital to support their performance in emergency tasks. Therefore, it is recommended to improve education, training facilities, and more regular scheduling to optimize the benefits of aerobic exercise.